Negotiation as a foundation in Islamic da'wah: Framework analysis on the memorandums held in the era of Rasullullah (pbuh) - Norhayati Rafida Abdul Rahim; Nurul Husna N.H.; Safiyyah A.S. (Kolej University Islam Sultan Azlan Shah, 2024)
Indexed by WOS